Effects of precompetitive preparation period on the isokinetic muscular characteristics in world class handball players - Maurelli, O.; Bernard, P. L.; Dubois, R.; Ahmaidi, S.; Prioux, J. (The Journal of Strength and Conditioning Research, 2019)
The aim of this study was to describe the effects of 8 weeks of precompetitive preparation period (Pc2P) on the isokinetic muscular characteristics in world-class handball players. Nineteen male professional players (age, 26.6 ± 5.4 years) participated in the study. Two bilateral isokinetic tests of knee joint flexors (H; hamstring) and extensors (Q; quadriceps) were performed before and after Pc2P to determine the peak torque (PT), the mean power (MP), and the ratios (agonist-antagonist, dominant-nondominant, and combined). For the PT, Q at low angular velocity (60°/s) in concentric mode revealed no significant increase for the dominant or nondominant legs. For H, results showed a significant increase for both legs (p < 0.001). At the higher angular velocity (240°/s), Q was significantly increased for the dominant (p < 0.005) and nondominant (p < 0.002) legs and also H for both sides (p < 0.001). Eccentric mode (30°/s) showed a significant increase for dominant (p < 0.005) and nondominant (p < 0.01) legs. For MP, results showed significant increase at low angular velocity (p < 0.003) and high angular velocity (p < 0.01) for both legs. In eccentric mode, values showed a significant increase after Pc2P for dominant (p < 0.001) and nondominant (p < 0.02) legs. The ratios showed significant increase for the agonist-antagonist ratio at 60°/s for dominant leg (p < 0.003) and the nondominant leg (p < 0.01). At 240°/s, the values showed a significant difference for both side (p < 0.02). From an injury risk perspective, in addition to optimizing performance, these results demonstrated that 8 weeks of Pc2P increased the maximum strength and muscle power of international handball players, even if the ratios of the knee joint muscles did not change during this period.